2018
DOI: 10.1038/s41598-018-27055-3
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of high-throughput screening data and novel mechanistic insights into VDR-xenobiotic interactions by orthogonal assays

Abstract: High throughput screening (HTS) programs have demonstrated that the Vitamin D receptor (VDR) is activated and/or antagonized by a wide range of structurally diverse chemicals. In this study, we examined the Tox21 qHTS data set generated against VDR for reproducibility and concordance and elucidated functional insights into VDR-xenobiotic interactions. Twenty-one potential VDR agonists and 19 VDR antagonists were identified from a subset of >400 compounds with putative VDR activity and examined for VDR function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
(63 reference statements)
1
4
0
Order By: Relevance
“… Hsu et al (2016) observed as similar phenomena where select FXRα antagonists enhanced humanFXRα:coregulator interactions in the presence of CDCA. These results are also similar to that observed with vitamin D receptor antagonists ( Mahapatra et al, 2018 ) suggesting that this process is not unique to human or medaka FXRα. Rather, this finding suggests that alternate mechanisms may be associated with receptor inhibition in lieu of coactivator recruitment.…”
Section: Discussionsupporting
confidence: 86%
“… Hsu et al (2016) observed as similar phenomena where select FXRα antagonists enhanced humanFXRα:coregulator interactions in the presence of CDCA. These results are also similar to that observed with vitamin D receptor antagonists ( Mahapatra et al, 2018 ) suggesting that this process is not unique to human or medaka FXRα. Rather, this finding suggests that alternate mechanisms may be associated with receptor inhibition in lieu of coactivator recruitment.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, because of the low cost of the zebrafish model, it could be key in providing a functional screen for determining which environmental chemicals and drugs run the risk of disrupting neurobehavioral function with developmental exposure. This is advantageous particularly coupled with high-throughput in vitro screens such as those already utilized to identify compounds with the potential for interfering with VDR signaling [24].. The results of the current study demonstrate the behavioral impairments in adults that result from dietary vitamin D deficiency throughout development.…”
Section: Discussionmentioning
confidence: 62%
“…For example, Cd 2+ has been observed to substitute for Zn 2+ in the zinc finger DNA-binding domain of the estrogen receptors [9]. It has been demonstrated through high throughput screening that the VDR is activated or antagonised by a wide range of chemicals, including metals (Cd) [102]. If downstream effects are blocked or altered this could potentially increase the metabolism of vitamin D and reduce 25OHD.…”
Section: Endocrine Disruption -Toxic Metals Disrupt the Vitamin D End...mentioning
confidence: 99%